2018
DOI: 10.1177/1937586718810878
|View full text |Cite
|
Sign up to set email alerts
|

Attractions to Fuel the Imagination: Reframing Understandings of the Role of Distraction Relative to Well-Being in the Pediatric Hospital

Abstract: Objective: Ulrich’s (1991) definition of “positive distraction” includes that which “elicits positive feelings and holds attention,” implying that the capacity of an environmental feature to hold attention is a necessary component. This article examines whether, in the context of a pediatric hospital, a distraction needs to “hold attention” to secure positive benefits for patient well-being. Background: Data collected from 246 patients at Melbourne’s Royal Children’s Hospital (Australia) revealed a discrepancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Many of the publications in our sample, however, used complimentary data collection methods, such as interview or questionnaire, to supplement and enhance their observation (see right-hand column Table 2). Some of the studies which produced nonspecific findings from their observation data were able to draw more specific conclusions once these findings were merged with results from other data collection methods (Johnson & Delaney, 2006; Macdonald et al, 2012), especially where mixed methods were used (Anåker et al, 2018; Broom et al, 2019; McLaughlan et al, 2019; Shepley, 2002). For example, McLaughlan et al used surveys, drawings, and photo-elicitation interviews to complement spatial observation methods in their study of children’s behavior in waiting areas of a pediatric hospital (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the publications in our sample, however, used complimentary data collection methods, such as interview or questionnaire, to supplement and enhance their observation (see right-hand column Table 2). Some of the studies which produced nonspecific findings from their observation data were able to draw more specific conclusions once these findings were merged with results from other data collection methods (Johnson & Delaney, 2006; Macdonald et al, 2012), especially where mixed methods were used (Anåker et al, 2018; Broom et al, 2019; McLaughlan et al, 2019; Shepley, 2002). For example, McLaughlan et al used surveys, drawings, and photo-elicitation interviews to complement spatial observation methods in their study of children’s behavior in waiting areas of a pediatric hospital (2019).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of distractive coping can be a risk factor for depressive symptoms and may be indicative of avoidance and maladaptive responses in the presence of stressful life events (Gross & John, 2003;Korpela et al, 2018;Tull et al, 2004). Likewise, an overreliance on rumination is characteristic of perseverating on negative events, a known precursor of depression (Hudson Banks et al, 2006;McLaughlan et al, 2019) in the context of racial discrimination. These extremes in coping response may paralyze assets that would have otherwise been useful when facing stress like racial discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature examining the role of coping strategies for adolescents and the consensus is that adolescents and emerging adults use distraction (i.e., refocusing one's attention away from the stressful event) to negate negative mood states leading, in turn, to better psychological wellbeing (Broderick, 2005;Ito et al, 2003;Korpela et al, 2018). The literature suggests that distractive coping can decrease the severity of depressive symptoms in adolescents and adults in the short term (Gaylord-Harden, Gipson, Mance, & Grant, 2008;McLaughlan, Sadek, & Willis, 2019;Nolen-Hoeksema et al, 1994;Wolgast & Lundh, 2017), but may cause harm in the long term in the form of avoidance or suppression of distress (Blalock & Joiner, 2000;Gross & John, 2003;Tull, Gratz, Salters, & Roemer, 2004;Wolgast & Lundh, 2017).…”
Section: Distractive Copingmentioning
confidence: 99%
“…It has been reported that passive distraction can reduce patients' anxiety and pain and reduce perceived waiting time [31]. In a study conducted at the Royal Children's Hospital in Melbourne, environmental characteristics were found to enhance patients' willingness to visit the hospital and even improve their health [32]. Exposure to nature, music and art, as well as uncrowded and peaceful environments, can enhance the pediatric healthcare building environment [33].…”
Section: Pediatric Waiting Roomsmentioning
confidence: 99%